Working with the whole family: what case files tell us about social work practices - Laird, Siobhan E.; Morris, Kate; Archard, Philip; Clawson, Rachael (Wiley, 2017)
Practice theories to support child protection social work in the United Kingdom, as in the United States and Australia, are being squeezed out by a focus on performance targets and procedural timescales. This study examines an innovative programme designed to reverse this trend initiated by an English local government authority. The programme aimed to embed systemic family practice in situations where children are deemed to be at risk of harm. The findings, derived from an analysis of a case file sample, indicate that social worker interaction with family members is predicated on who is living with the child in conjunction with the risk status of the case file. Conversely, practitioner interactions with family members are divorced from family structure and the lived experiences of kin relationships. This study concludes by examining why, despite training in systemic family practice, it was problematic for social workers to integrate it into their encounters with families.